2010
DOI: 10.4014/jmb.0904.04015
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic Effects of Fermented Ixeris sonchifolia and Its Constituent in Mice

Abstract: To evaluate the antiallergic effect of fermented Ixeris sonchifolia (IS, family Compositae), we prepared IS kimchi, isolated lactic acid bacteria (LAB) from it, fermented IS with these LAB, and investigated their antiallergic effects. IS kimchi inhibited the passive cutaneous anaphylaxis (PCA) reaction induced by an IgE-antigen complex as well as the scratching behavior induced by compound 48/ 80 or histamine more potently than IS. When IS was fermented with LAB isolated from IS kimchi, its antiallergic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Systemic administration of chlorogenic acid has been reported to cause partial inhibition of scratching induced by histamine and mast cell degranulation (6). A topical dose of 5% chlorogenic acid might not be enough to exert anti-histamine effects in the dermis.…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of chlorogenic acid has been reported to cause partial inhibition of scratching induced by histamine and mast cell degranulation (6). A topical dose of 5% chlorogenic acid might not be enough to exert anti-histamine effects in the dermis.…”
Section: Short Communicationmentioning
confidence: 99%
“…Extracts of plants of Prunus species, especially cherry trees, have several pharmacological effects, including antiinflammatory, anti-hyperlipidemic, anti-hyperpigmentation, and antioxidant effects (4,5). It has been recently reported that systemic administration of chlorogenic acid, a main constituent of cherry leaves, exerts weak inhibitory activity on hind-paw scratching induced by histamine and plasma extravasation induced by passive cutaneous anaphylaxis in mice (6). Therefore, in the present study, we examined the effects of topical application of chlorogenic acid on sodium laurate-induced scratching and the mechanisms of anti-pruritic activity of topical chlorogenic acid.…”
Section: Short Communicationmentioning
confidence: 99%
“…In addition, there also some studies showed that ISH provide a neuroprotective effects against ischemiainduced cellular injury in vitro [13], and inhibition the cell proliferation in HepG2 human hepatocellular carcinoma cells [14]. More importantly, in animal model experiment, ISH showed a potent anti-allergic effects in mice model [15], anti-tumors in non-small cell lung cancer in animals [16], and anti-human hepatocellular carcinoma in mice model [14]. Furthermore, the constitutes study of the ISH showed that the main bioactivity component mainly contains flavonoid [17], sesquiterpene lactone [18,19], sesquiterpene lactone glucoside [20], triterpenoidal saponin [21][22][23] and etc..…”
Section: Introductionmentioning
confidence: 99%
“…The IgE receptor activates the JNK pathway through the MEKK2-MKK4/7 cascade [8,9]; this pathway is essential for the induced expression of some cytokine genes such as IL-4, IL-6, or TNF-α and is activated following antigenic mast cell activation [10,11]. These cytokine-induced reactions then cause tissue inflammation and anaphylaxis, both of which are becoming chronic health problems worldwide [12].…”
Section: Introductionmentioning
confidence: 99%